Construct Validity and Reliability of the Mindfulness and Equanimity Inventory - Moscoso, Manolete S. (2020)
The purpose of this study is to report evidence of construct validity and reliability of a new self-report instrument that measures mindfulness and equanimity in a Spanish speaking population. An initial pool of 26 items was evaluated by 17 experts from Spain and Latin America and modified on the basis of their comments. The resulting list of 21 items was administered to 746 university students in Mexico and Peru. Their responses were analyzed using Unweighted Least Squares (ULS) with promin rotations. Two factors were identified, mindless and mindful, with factor loadings ranging from .36 to .65. The reliability coefficients for the first and second factors were .78, and .82 respectively. The inter-factors correlation was -.51. The results indicate clear evidence of convergent and discriminative validity.